Eculizumab for acute relapse of neuromyelitis optica spectrum disorder: Case report - Chatterton, Sophie; Parratt, John Douglas Edward; Ng, Karl (Frontiers in Neurology, 2022)
Introduction Eculizumab has been shown to be an effective and typically well-tolerated medication in the treatment of neuromyelitis optica spectrum disorder (NMOSD) in maintaining disease remission in patients who are aquaporin-4 water channel autoantibody (AQP4-IgG) seropositive. The efficacy of eculizumab in an acute relapse of NMOSD however is still under review. Case We describe a 46 year-old female who presented with acute left monocular vision loss on a background of bilateral optic neuritis treated 15 years prior as suspected NMOSD. She had very poor vision from the right eye (6/60). On presentation she was not on any long-term immunosuppressive agents. Her serum was positive for AQP4-IgG and MRI brain and spine demonstrated areas of demyelination in the corpus callosum and thoracic spine. She was treated with high dose intravenous methylprednisolone and underwent plasmapheresis for five consecutive days, but continued to clinically deteriorate with ongoing blindness in her left eye (light perception only). She was subsequently administered eculizumab with weaning oral corticosteroids. Clinically her vision improved to counting fingers and she remains on maintenance eculizumab infusions in the community. At 3 months, there is a steady improvement but still significant loss of central vision from that eye. Conclusion The utility of eculizumab in NMOSD may assist with treating acute episodes. This theoretically accords with the mode of action in inhibiting conversion of C5–C5a/b, perhaps arresting the acute inflammatory process in this disease. Given that disease burden and mortality in NMOSD is almost entirely related to relapses, increased use of eculizumab acutely could potentially aid recovery from an attack in very severe attacks, and therefore minimize immediate stepwise accrual of disability.